Reveromycins A and B from Streptomyces sp. 3–10: Antifungal Activity against Plant Pathogenic Fungi In vitro and in a Strawberry Food Model System - Lyu, Ang; Liu, Hao; Che, Hongjie; Yang, Long; Zhang, Jing; Wu, Mingde; Chen, Weidong; Li, Guoqing (Frontiers in Microbiology, 2017)
This study was conducted to determine the antifungal activity of the metabolites from Streptomyces sp. 3-10, and to purify and identify the metabolites. Meanwhile, the taxonomic status of strain 3-10 was re-evaluated. The cultural filtrates of strain 3-10 in potato dextrose broth were extracted with ethyl acetate. The resulting crude extract at 1 and 5 μg/ml inhibited growth of 22 species in 18 genera of plant pathogenic fungi and Oomycetes, accounting for 92% of the total 24 tested species, suggesting that it has a wide antifungal spectrum. Two compounds were purified from the crude extract and were identified as reveromycins A and B, which demonstrated high antifungal activity against Botrytis cinerea, Mucor hiemails, Rhizopus stolonifer, and Sclerotinia sclerotiorum under acidic pH conditions. Both the crude extract and reveromycin A from strain 3-10 at 10, 50 and 100 μg/ml showed high efficacy in suppression of strawberry fruit rot caused by the above-mentioned four pathogens. The efficacy was comparable to that of corresponding commercial fungicides (pyrimethanil, captan, dimetachlone) used in management of these pathogens. Morphological, physiological and phylogenetic characterization showed that strain 3-10 is closely related to Streptomyces yanglinensis 1307 T, representing a novel phylotype in that species. This study reported a new strain with reveromycins-producing capability. The finding is important for further exploitation of reveromycins for agricultural use.